TINGKAT KEMATANGAN GONAD KEPITING BAKAU Scylla paramamosain Estampador DI HUTAN MANGROVE TELUK BUO KECAMATAN BUNGUS TELUK KABUNG KOTA PADANG - Samsu, Fetro Dola; Sumarmin, Ramadhan; Zeswita, Armein Lusi (Pendidikan Biologi, 2013)
Abstract:Scylla paramamosain E. is one type of crab that lives in mud substrat at mangroveareas Buo Gulf. Scylla Paramamosain E. is favored by the people in the Buo Gulf. Now Scylla paramamosain E. population has begun to decrease and sizes caught are relatively small . Based on at this research take plan to identification gonad maturity of Scylla paramamosain E. at mangrove forest in the Buo Gulf Bungus of Padang. This study was conducted in May until July 2013 used the descriptive method. The results showed there were different gonad maturity of Scylla paramamosain was caught in the Buo Gulf. In May, Scylla paramamosain E. had immature gonads 33.33 % while the percentage of matured at a rate of66.67 % . In June, the percentage of immature gonads and matured amount 30.0% and 70 % . In July, there were 41 , 66 % in the immature stage and 58.32 % matured. Among of the three months, gonad maturity Scylla paramamosain E in July at the mostly mature gonad condition and ready for spawning. In addition biogeochemical cycles can influence and bring sufficient nutrients for survival Scylla paramamosain E. In general the level gonad maturity in Scylla paramamosain E. in the Gulf Buo mangrove forest in May to July 2013 TKG I5.68 % , 29.32 % TKG II , III TKG 21.27 % , 11.15 % IV TKG , TKG V 32.59 %. Environmental factors such as temperature measured during the study ranged from 280C , salinity ranges from 31 % o - 32 % o , pH around 7 ( Neutral ) and an average water depth of 58.5 cm .